Analisis Pelaksanaan Sistem Pengendalian Intern Pemerintah di Indonesia - Ompusunggu, Sensia Gibsi; Salomo, Roy Valiant (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Law Number 1 of 2004 concerning State Treasury Managing Government Systems in Indonesia. The Government of Indonesia has issued Government Regulation Number 60 of 2008 concerning the Government's Internal Control System. Since the stipulation of Government Regulation Number 60 of 2008 has been approved for 10 years the regulation has been applied. However, the policy contained in Government Regulation Number 60 of 2008 has not been fully approved in Indonesia. The results of the government's internal control system maturity evaluation of the maturity level of SPIP are still far from the Government's target. In addition, the Supreme Audit Agency also found weaknesses in the Indonesian Government's internal supervision system in 2015-2017 inspections. Things that hinder the implementation of the government's internal control system in Indonesia include: (a) Weakness in terms of content and policy context; (b) There is no effect of applying sanctions; (c) Less consideration, according to consideration; (d) Error in agreement; (e) Management neglect; and (f) Collusion.